Tanggap fungsional predator Menochilus sexmaculatus (Fabricius) dan Micraspis lineata (Thunberg) (Coleoptera: Coccinellidae) terhadap kutukebul Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) dan kutudaun Myzus persicae (Sulzer) (Hemiptera: Aphididae) - Purnama Hidayat; Van Basten Tambunan; Keisha Disa Putirama (Jurnal Entomologi Indonesia, 2021)
The whitefly, Bemisia tabaci (Gennadius) and the aphid, Myzus persicae (Sulzer) are important pests in tomato and chilli pepper. These pests directly attack and as a viral vector can decrease the production of tomato and chili pepper. Menochilus sexmaculatus (Fabricius) and Micraspis lineata (Thunberg) are predator beetles of B. tabaci and M. persicae. This study aimed to know the potential predation of M. sexmaculatus and M. lineata as a predator of B. tabaci and M. persicae. Completely randomized factorial design using 2 factors consist of type and density of prey with 3 replicates used in this study. The potency of predatory coccinellidae as predator of B. tabaci and M. persicae was evaluated in 2 observations, i.e. predation and functional response assay. Based on logistic regression analysis, both of M. sexmaculatus and M. lineata showed characteristic of type I functional, this means that the higher density of prey, the ability and predation rate of M. sexmaculatus and M. lineata were also increased. The predator M. sexmaculatus and M. lineata were more effective to control M. persicae than B. tabaci.  M. sexmaculatus was the effective predator to control adult of M. persicae.